Isolated teeth from La Ferrassie: Reassessment of the old collections, new remains, and their implications. Issue 1 (16th February 2019) - Becam, Gaël; Verna, Christine; Gómez‐Robles, Aida; Gómez‐Olivencia, Asier; Albessard, Lou; Arnaud, Julie; Frelat, Mélanie A.; Madelaine, S.; Schwab, Catherine; Souday, Caroline; Turq, Alain; Balzeau, Antoine
Abstract: Objectives: We provide the description and comparative analysis of six new teeth from the site of La Ferrassie. Our goal is to discuss their taxonomic attribution, and to provide an updated inventory of Neandertal and modern human remains from La Ferrassie in their associated archeological context. Materials and methods: We use external and internal anatomy, classic morphometrics, and geometric morphometrics. The teeth from La Ferrassie are compared to several samples of contemporary Neandertals and upper Paleolithic modern humans and to recent modern humans. Results: Three specimens are classified as Neandertals, two as modern humans, and one remains unclassified. Discussion: Based on the previously known fossil samples and the new teeth reported here, there are currently a minimum of four adult and five immature Neandertal individuals coming from the "Grand Abri" and a minimum of two modern human adult individuals: one from "Grand Abri" and one from "Grotte." It is noteworthy that the spatial distribution of the recovered Neandertal remains is not restricted to the area where the LF1–LF 8 were found but now covers the full extension of the excavated area. Moreover, while both Neandertal and modern human occupations have yielded isolated human remains, the partial‐to‐complete skeletons only belong to Neandertals. These considerations open new perspectives for the understanding of the occupation and use of the La Ferrassie site.